Chinese antiquities an introduction to the art market - Wang, Audrey (Farnham Burlington, Vermont Lund Humphries London New York In association with Sotheby's Institute of Art, 2012)
Chinese Antiquities: An Introduction to the Art Market provides an essential guide to the growing market for Chinese antiquities, encompassing all sectors of the market, from Classical Chinese paintings and calligraphy to ceramics, jade, bronze and ritual sculpture.
A global trade. Geopolitical issues for the People's Republic of China ; Historical trade in Chinese material culture ; The global market today -- Today's Chinese art market sectors. Traditional painting and calligraphy ; Chinese ceramics ; Decorative works of art -- The structure of the art market. Museums and public collections ; Collectors and the art of collecting Chinese antiques ; Chinese art and antique dealers ; Chinese art auctions.
Keywords: Antiques -- China; Antiques business -- China